Multifaktor Penyebab Gizi Kurang pada Balita: Studi Kuantitatif di Deli Serdang, Sumatera Utara - Fadhilah Setyorini; Zuraidah Nasution; Arifah Devi Fitriani (Jurnal Kesehatan Amanah, 2025)
Nutritional status of toddlers is a crucial indicator of children's health quality and the nation's future development. This study aimed to analyze the factors associated with undernutrition among toddlers in the working area of Hamparan Perak Health Center in 2024. A quantitative approach with a cross-sectional design was used. A total of 32 toddlers with undernutrition were selected using purposive sampling. Data were collected through structured questionnaires and interviews, and analyzed using univariate and bivariate analysis with chi-square tests. The results revealed significant associations between maternal education, maternal nutritional knowledge, family income, feeding patterns, and exclusive breastfeeding with toddler nutritional status (p < 0.05). Toddlers raised by mothers with low education and poor knowledge, from low-income families, with poor dietary patterns, and who were not exclusively breastfed were at higher risk of being undernourished. This study recommends an integrated intervention strategy involving nutrition education, economic empowerment, and exclusive breastfeeding promotion to reduce the prevalence of undernutrition among toddlers.